Penerapan Tri-N dalam Buku Teks Siswa Bahasa Indonesia untuk Siswa SMP Kelas VIII Kurikulum 2013 - Siti Rahayu; Siti Rochmiyati (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2019)
The purpose of this study was to describe the application of the Niteni, Nirokke, and Nambahi processes in Indonesian Students' Textbooks for Class VIII Junior High School Students in 2013 Curriculum. The research method uses a qualitative descriptive method with the interactive analysis model of Miles and Huberman. Data collection techniques using documentation techniques sourced from students' textbooks, namely Indonesian Language Books for Students of Class VIII Middle School Curriculum 2013. Data in this study are words, phrases, sentences, and paragraphs that contain operational verbs in the application of the niteni, nirokke, and nambahi to the student textbook. Test the validity of the data using member check and expert validation. Data analysis techniques with the following steps: data reduction, data presentation, and verification or conclusion. The results showed that all indicators of the niteni, nirokke, and nambahi processes were contained in the textbook. Niteni in students' textbooks has the element of observing using the sense of hearing, digging deeper information from observations, and reasoning by connecting knowledge already possessed from excavated results. Nirokke in students' textbooks has the elements of imitating through sound, imitating by reading, imitating by writing, imitating through movement, imitating by trying or experimenting, imitating by demonstrating or practicing, and imitating by presenting. Then, Nambahi in student textbooks there is an element of adding by creating or making, and the process of adding by improvising.